Effects of remote ischemic preconditioning on contrast induced nephropathy after percutaneous coronary intervention in patients with acute coronary syndrome. Issue 2 (January 2018) - Zhou, Fazhan; Song, Wei; Wang, Zilong; Yin, Luhua; Yang, Shen; Yang, Fubai; Song, Zhaofeng; Song, Yaguang; Zhang, Huanyi; Qiao, Fengjie; Zhang, Zhimian
Abstract: Objective: The aim of this study was to explore the clinical effects of remote ischemic preconditioning (RIPC) on contrast-induced nephropathy after percutaneous coronary intervention (PCI) in patients with acute coronary syndrome (ACS). Patients and Methods: The study was a single-center, prospective, randomized, controlled study. A total of 161 patients with ACS and the rate of estimate glomerular filtration (eGFR) 15 to 70 mL/min/1.73 m2 undergoing PCI were randomly assigned to RIPC group (induced by 4 times of 5-minute inflations of a blood pressure cuff to 200 mmHg around the upper arm, followed by 5-min intervals of reperfusion at 1 hour before PCI therapy) or control group (an uninflated cuff around the arm). Successful completion of the PCI eventually included 107 cases of patients, including 50 cases in the RIPC group and 57 cases in the control group. The level of serum creatinine (Scr), CystatinC (CysC), blood neutrophil gelatinase-associated lipocalin (NGAL), eGFR were measured in all patients at 6 AM before the day of PCI, and 4-hour NGAL, 24-hour CysC, 72-hour Scr, and eGFR after PCI in the 2 groups. The incidence of major adverse events in the kidney (including the incidence of CIN, the need for dialysis, or renal replacement therapy after using contrast agent) and the composite endpoint of cardiovascular events were recorded at 6 months after PCI. Results: There were no statistically significant differences in baseline indicators between the 2 groups. Scr, CysC, and blood NGAL levels and the incidence of CIN in patients with RIPC group were significantly lower than those form the control group after PCI ( P  < .05), but there were no significant differences between the average value of eGFR and occurrence of Major cardiovascular events in the postoperative 6 months ( P  > .05). Conclusions: RIPC can reduce PCI-related CIN and protect renal function in patients with ACS. The benefits of these patients by RIPC may be related to the reduction of the NGAL and CysC.